Event-driven molecular dynamics of soft particles - Müller, Patric; Pöschel, Thorsten (Physical Review E, 2013)
The dynamics of dissipative soft-sphere gases obeys Newton's equations of motion, which are commonly solved numerically by (force-based) Molecular Dynamics (MD) schemes. With the assumption of instantaneous, pairwise collisions, the simulation can be accelerated considerably using event-driven MD, where the coefficient of restitution is derived from the interaction force between particles. Recently it was shown, however, that this approach may fail dramatically, that is, the obtained trajectories deviate significantly from the ones predicted by Newton's equations. In this paper, we generalize the concept of the coefficient of restitution and derive a numerical scheme which, in the case of dilute systems and frictionless interaction, allows us to perform highly efficient event-driven MD simulations even for noninstantaneous collisions. We show that the particle trajectories predicted by our scheme agree perfectly with the corresponding (force-based) MD, except for a short transient period whose duration corresponds to the duration of the contact. Thus, the new algorithm solves Newton's equations of motion like force-based MD while preserving the advantages of event-driven simulations. © 2013 American Physical Society.